2019
DOI: 10.1096/fj.201802007r
|View full text |Cite
|
Sign up to set email alerts
|

MAPK inhibition and growth hormone: a promising therapy in XLH

Abstract: X‐linked hypophosphatemia (XLH) leads to growth retardation and bone deformities, which are not fully avoided by conventional treatment with phosphate and vitamin D analogs. Pediatric patients have been treated with growth hormone (GH), and recent findings suggest that blocking fibroblast growth factor 23 actions may be the most effective therapy, but its effects on growth are not known. We here report the effect of MAPK inhibition alone or associated with GH on growth and growth plate and bone structure of yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…7 Growth hormone therapy can be beneficial in children with XLH, 9,23,24 and in the Hyp mouse model of XLH. 10 Haffner and colleagues found improved growth rate and median adult height in three children in whom rHGH was initiated before puberty for 3.1−6.3 years. However, the upper/lower ratio was exaggerated in some.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 Growth hormone therapy can be beneficial in children with XLH, 9,23,24 and in the Hyp mouse model of XLH. 10 Haffner and colleagues found improved growth rate and median adult height in three children in whom rHGH was initiated before puberty for 3.1−6.3 years. However, the upper/lower ratio was exaggerated in some.…”
Section: Discussionmentioning
confidence: 98%
“…Recombinant human growth hormone (rHGH) therapy has been used with some benefit in patients with XLH and the Hyp mouse model of XLH. 9 , 10 This may be due, in part, to the calcium- and phosphate-sparing effects of GH and IGF1 in the kidneys. 11 13 In seven children with idiopathic GH deficiency, intestinal calcium absorption increased during rHGH administration, resulting in a compensatory decrease of PTH and serum 1,25(OH) 2 D, and, thus, was interpreted as direct effect of rHGH at the intestinal lining.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the disease was similar in males and females. Background X-linked hypophosphatemic rickets (XLH) (OMIM 307800) is the most common hereditary rickets (1)(2)(3)(4)(5) with an estimated prevalence of 1:20,000 (6,7). It follows a dominant transmission (8).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a young hyp mice model demonstrated that the combination of MAPK inhibitor, which heals rickets and improves growth plate organisation, along with GH could be a promising new therapy in treating children with XLH. However, such therapy would need exploration via clinical trials in humans [45].…”
Section: Mapk Inhibitorsmentioning
confidence: 99%